Faktor – Faktor yang Berhubungan dengan Kejadian Kekerasan dalam Rumah Tangga di Kelurahan Bojong Baru - Pirez, Rosalina Gastao; Novita, Regina Vidya Trias; Simbolon, Anna Rejeki (Universitas Malahayati, 2025)
ABSTRACT Based on WHO data, one in three (35%) women in the world have experienced physical and or sexual violence committed by their husbands or non-intimate partners. Efforts have been made for legal protection by making Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law). Domestic violence can cause physical, psychological, sexual, and economic misery. The purpose of this study was to identify factors associated with the incidence of domestic violence in Bojong Baru Village. The research design used is quantitative cross-sectional technique approach. Sample 102 respondents with purposive sampling technique. The results showed there was a relationship between income (0.016); age of marriage (0.018); occupation (0.006) with the incidence of domestic violence in Bojong Baru Village. The lack of knowledge makes victims accustomed to the violence experienced. Conclusion Domestic violence knowledge must be given early so that it is easy to recognize and overcome as early as possible. It is recommended that the family and local environment supported by the local government participate in promotive and preventive measures against the incidence of domestic violence Keywords: Violence, Income, Age of Marriage, Occupation, Knowledge ABSTRAK Berdasarkan data WHO satu dari tiga (35%) wanita di dunia pernah mengalami kekerasan fisik dan atau seksual yang dilakukan oleh suami maupun non-pasangan intim mereka. Upaya yang telah dilakukan perlindungan hukum dengan membuat UU Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga (UU PKDRT). KDRT dapat membuat kesengsaraan secara fisik, psikologis, seksual, maupun ekonomi. Tujuan penelian ini adalah mengidentifikasi faktor – faktor yang berhubungan dengan kejadian KDRT di Kelurahan Bojong Baru. Desain penelitian yang digunakan adalah kuantitatif pendekatan teknik cross – sectional. Sampel 102 responden dengan teknik purposive sampling. Hasil menunjukkan ada hubungan antara pendapatan (0.016); usia pernikahan (0.018); pekerjaan (0.006) dengan kejadian KDRT di Kelurahan Bojong Baru. Tingkat pengetahuan yang kurang membuat korban terbiasa dengan kekerasan yang dialami. Kesimpulan pengetahuan KDRT harus diberikan sejak dini agar mudah dikenali dan diatasi sedini mungkin. Sebaiknya keluarga dan lingkunagn setempat didukung oleh pemerintah daerah ikut serta dalam tindakan promotif dan preventif terhadap kejadian KDRT. Kata Kunci: Kekerasan, Ekonomi, Usia Pernikahan, Pekerjaan, Tingkat Pengetahuan